Hypohidrotic ectodermal dysplasia and immunodeficiency with coincident NEMO and EDA Mutations - Keller, Michael D.; Petersen, Maureen; Ong, Peck; Church, Joseph; Risma, Kimberly; Burnham, Jon; Jain, Ashish; Stiehm, E. R.; Hanson, Eric P.; Uzel, Gulbu; Deardorff, Matthew A.; Orange, Jordan S. (Frontiers in Immunology, 2011)
Ectodermal dysplasias (ED) are uncommon genetic disorders resulting in abnormalities in ectodermally-derived structures. Though many ED-associated genes have been described, the NF-κB Essential Modulator (NEMO encoded by the IKBKG gene) is unique in that mutations also result in severe humoral and cellular immunologic defects. We describe three unrelated kindreds with defects in both EDA and IKBKG resulting from an X-chromosome crossover. This demonstrates the importance of thorough immunologic consideration of patients with ED even when an EDA etiology is confirmed, and raises the possibility of a specific phenotype arising from coincident mutations in EDA and IKBKB.